A new species of Scaris from southeastern Brazil, with notes on S. nessimiani and S. bahiensis (Homoptera: Cicadellidae) - Nova Coelho, Luci Boa; Ribeiro Da-Silva, Elidiomar (Revista de Biología Tropical, 2002)
Anew leafhopper species, Scaris angrensis sp.nov., is described and illustrated based on an adult male from Angra dos Reis, State of Rio de Janeiro, southeastern Brazil. The holotype is deposited in the entomological collection of Museu Nacional, Universidade Federal do Rio de Janeiro, Brazil. The new species seems to be more closely related to S. bahiensis because of its single ventral process on the aedeagal base, being distinguished from that by the apical shape of the stylus. A problem related to the illustrations in the original description of S. nessimiani and S. bahiensis is herein corrected.